The Internet-Based Conversational Engagement Clinical Trial (I-CONECT) in Socially Isolated Adults 75+ Years Old: Randomized Controlled Trial Protocol and COVID-19 Related Study Modifications - Yu, Kexin; Wild, Katherine; Potempa, Kathleen; Hampstead, Benjamin M.; Lichtenberg, Peter A.; Struble, Laura M.; Pruitt, Patrick; Alfaro, Elena L.; Lindsley, Jacob; MacDonald, Mattie; Kaye, Jeffrey A.; Silbert, Lisa C.; et al. (Frontiers in Digital Health, 2021)
Background: Increasing social interactions through communication technologies could offer a cost-effective prevention approach that slows cognitive decline and delays the onset of Alzheimer’s Disease. This paper describes the protocol of an active project named “Internet-based conversational engagement clinical trial (I-CONECT)” (ClinicalTrial.gov: NCT02871921). The COVID-19 pandemic related protocol modifications are also addressed in the current paper. Methods: I-CONECT is a multi-site, assessor-blind, randomized controlled behavioral intervention trial (RCT). We aim to randomize 320 socially isolated adults 75+ years old (160 Caucasian and 160 African American participants, 50:50 split between those with normal cognition and mild cognitive impairment (MCI)) recruited from the community to either the Video Chat Intervention Group or the Control Group (1:1 allocation). Those in the Video Chat Group receive a computer and internet service for the duration of the study, which they use to video chat with study staff for 30 minutes/day 4x/week for 6 months (high dose), and then 2x/week for an additional 6 months (maintenance dose). Both Video Chat and control groups will have a brief (about 10 minutes) telephone check-in with study staff once per week. The primary outcome is the change in global cognitive function measured by Montreal Cognitive Assessment (MoCA) from baseline to 6 months. Secondary outcomes include changes in cognition in memory and executive function domains, emotional well-being measured by NIH Toolbox emotional battery, and daily functional abilities assessed with the Revised Observed Tasks of Daily Living (OTDL-R). Eligible participants have MRIs at baseline and 6 months. Participants contribute saliva for genetic testing (optional consent), and all video chat and neuropsychological assessment sessions are recorded for speech and language analysis. The pandemic halted research activities and resulted in protocol modifications, including replacing in-person assessment with remote assessment, remote deployment of study equipment, and revised targeted sample size. Discussion: This trial provides user-friendly hardware for the conversational-based intervention that can be easily accessed at participants’ homes. The trial aspires to use age and culture-specific conversational materials and a related platform developed in this trial for enhancing cognitive reserve and improving cognitive function.